Design and characterization of multiwavelength fiber laser in o-band transmission window / Siti Fatimah Norizan - Siti Fatimah, Norizan (2015)

(untitled)
This thesis presents the research work that has been carried out on O-band transmission windows as support to the saturated optical fiber transmission windows. O-band is selected based on advantages it offer including operational cost effectiveness, low absorption coefficient, low dispersion wavelength range and operated with existence system. The aim of this research work is to investigate the components that could be used in developing O-band as transmission windows. The components studied in this research work are the optical amplifiers and multiwavelength fiber laser as the transmitter. The optical amplifiers are Bismuth doped fiber amplifier (BiDFA), O-band Raman fiber amplifier (RFA) and Booster optical amplifier (BOA). The BiDFA produce low amplification (~2 dB) but high nonlinearity coefficient measured to be 13.98 W-1 km-1 utilizing the four wave mixing (FWM) effect. The RFA was tested with 4 different types of fiber, where dispersion compensated fiber (DCF) shows the highest amplification performance with gain of 12 dB for single pass configuration and 14 dB for double pass at 1330 nm signal wavelength. The BOA is an improved version of semiconductor optical amplifier (SOA) capable to amplify up to 28 dB and 31 dB at 1350 nm for single pass and double pass configuration respectively. The optical amplifier is not only use as the amplifier but also to support the process of generating multiwavelength fiber laser (MWFL). Three techniques demonstrated in this thesis include; multiwavelength Brillouin fiber laser (MWBFL), Sagnac loop mirror (SLM) and Fabry Perot Interferometer. The MWFL was demonstrated by various configurations to investigate the performance including its peak power flatness and tune ability. The MWBFL generated from nonlinear effect of stimulated Brillouin scattering (SBS). The Brillouin threshold power required to generate SBS in O-band is less than threshold of C-band. The MWBFL demonstrated in 2 different cavites namely linear cavity and ring cavity. Both cavities produce 4 Stokes with the linear cavity giving a iii closed spacing of 12.5 GHz while ring cavity 25 GHz. Inserting BOA in the multi pass linear configuration induce nonlinearity and hence produces 3 anti-Stokes signals. The flatness of MWBFL achieved via 2 techniques namely by in cooperate the BiDF in the cavity to provide FWM effects and by relocating the BOA. The spacing tunability for MWBFL is limited to two spacing 12.5 GHz and 25 GHz. Sagnac loop mirror were also demonstrated in linear and ring cavity, where the linear cavity provide stable and more number of channels (~16). The uniformity of MWFL via SLM was provided by the nonlinearity of BIDF. The tunability of the SLM is controlled by the length of polarization maintaining fiber (PMF). The FPI was only demonstrated in linear configuration. The spacing generated was double of SLM with the same length of PMF. The uniformity of peak power was also improved by the incorporation of BiDF. The tunability is achieved by controlling the polarization state. The spacing varied from 5.0 nm to 1.25 nm with 4 m PMF.